UNDERSTANDING GEN Z CONSUMER PREFERENCES FOR PRICING METHODS: A CASE STUDY IN CEBU, PHILIPPINES - Norberto M. Secretaria, Amelia Girly L. Aranas, Christina Y. Pacubas, Leovigilda L. Bithay (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study investigates how pricing methods affect the likelihood of purchase decisions made by Generation Z (Gen Z). Data from a sample of Gen Z buyers were gathered using a descriptive survey method in order to examine the different pricing indicators on their purchase behavior. The findings revealed that pricing strategies significantly play a role in the purchasing behavior of Gen Z consumers, and the mean scores of the different pricing categories indicate their importance in the decision-making process. The study identifies that value-based pricing is critical to Gen Z consumers, who place significant emphasis on the perceived value of products. Hence, aligning pricing with product value can increase the likelihood of purchase. The findings also indicate that regular discounts or promotional offers can trigger the behavioral tendency of motivating Gen Z consumers to make purchases. The results also suggest that pricing strategy has a substantial impact on consumer loyalty and brand-switching behaviors. Companies can use pricing as a tool to encourage brand loyalty and reduce the likelihood of customers switching to competitor products. Offering personalized pricing and loyalty rewards are some ways to strengthen brand-consumer relationships. Finally, the findings suggest that pricing strategies are crucial to the purchasing decisions of Gen Z consumers. Businesses must prioritize pricing as a vital component of their marketing strategy and tailor it to meet the needs and preferences of this demographic. The study contributes to the existing literature by providing insights into the role of pricing on Gen Z consumer behavior and providing recommendations for businesses seeking to target this demographic.